EXPERIMENTAL CHECK OF THE METHODS OF THE USE OF OPEN SYSTEM NETWORK TECHNOLOGIES IN THE FUTURE BACHELORS OF INFORMATICS - Vdovychyn, Т. Я. (Journal of Information Technologies in Education (ITE), 2018)
The article presents aspects of the use of open systems network technologies (OSNT) in universities. The efficiency of the use of OSNT for the interaction of participants in the educational process has been proved: students, faculty members, administration of higher educational institutions and teaching auxiliary staff. The results of the survey on the feasibility of introducing OSNT in the university's educational process have been demonstrated. The emphasis is placed on the use of OSNT in the process of preparation of Bachelors of informatics. Methodological aspects concerning the use of open systems network technologies in the training of future Bachelors of informatics provide the pedagogical feasibility of forms, methods and means of training. An important condition for the successful integration of the methodology of using OSNT is to improve the content of informatics disciplines (on the example of the discipline "Organizational Informatics"). In order to select the OSNT, it is necessary to take into account the links of use, users, technical means and their characteristics, risks (the impact of inaccurate, poor-quality information on the person, manipulation of human consciousness, access to personal data, lifting the prohibition and restrictions of moral and ethical character, etc.). The article deals with the problem of the formation of the competence of Bachelors of informatics on the use of open systems network technologies. The criteria, indicators and levels of competence of Bachelor of Informatics regarding the use of OSNT are determined. The main stages of the pedagogical experiment on the use of OSNT for future Bachelors of informatics are described. Experimental implementation of the results of the study showed that the application of a special methodology in the training of Bachelors of informatics contributes to the formation of competence in the use of OSNT.